Simultaneous NO/CO2 removal performance of biochar/limestone in calcium looping process. (15th February 2020) - Zhang, Wan; Li, Yingjie; Ma, Xiaotong; Qian, Yuqi; Wang, Zeyan
Highlights: Simultaneous NO/CO2 removal system using biochar/CaO in calcium looping is proposed. Coconut shell char/limestone shows good simultaneous NO/CO2 removal performance. CaO shows a strong catalysis effect on NO reduction by CO produced by char oxidation. Porous structure of biochar enhances NO reduction under calcium looping conditions. NO removal and CO2 capture efficiencies are above 97% and 80%, respectively. Abstract: A novel simultaneous NO/CO2 removal system using biochar and calcined limestone in the calcium looping process was proposed. Coconut shell char and calcined limestone were added into a carbonator in the calcium looping process as the NO reductant and CO2 sorbent, respectively. The simultaneous NO/CO2 removal performance of coconut shell char/calcined limestone in the calcium looping process was investigated in a bubbling fluidized bed reactor. NO and CO2 in flue gases are effectively and simultaneously removed by coconut shell char/calcined limestone in the presence of O2 . O2 plays an important role in NO removal by coconut shell char. The calcined limestone shows a strong catalytic effect on NO reduction by CO generated by the reaction of coconut shell char and O2 . The calcined limestone supports active sites for NO reduction by CO. High CO concentrations and high carbonation temperatures have positive effects on NO reduction by CO with calcined limestone catalysis. However, the catalytic effect of calcined limestone is weakened by its carbonation, which is promoted by the high temperature and additional CO2 produced by the oxidation of char. The simultaneous NO removal and CO2 capture efficiencies can reach above 97% and 80%, respectively. The porous structure of coconut shell char is an important factor in enhancing NO reduction with calcined limestone catalysis in the presence of O2 .